Diagnostic performance of noninvasive fractional flow reserve derived from coronary computed tomography angiography in suspected coronary artery disease: the NXT trial (Analysis of Coronary Blood Flow Using CT Angiography: Next Steps) - Norgaard, Bjarne L.; Leipsic, Jonathon; Gaur, Sara; Seneviratne, Sujith; Ko, Brian S.; Ito, Hiroshi; Jensen, Jesper M.; Mauri, Laura; De Bruyne, Bernard; Bezerra, Hiram; Osawa, Kazuhiro; Naber, Christoph; et al. (Journal of the American College of Cardiology, 2014)
The goal of this study was to determine the diagnostic performance of noninvasive fractional flow reserve (FFR) derived from standard acquired coronary computed tomography angiography (CTA) datasets (FFR(CT)) for the diagnosis of myocardial ischemia in patients with suspected stable coronary artery disease (CAD).FFR measured during invasive coronary angiography (ICA) is the gold standard for lesion-specific coronary revascularization decisions in patients with stable CAD. The potential for FFR(CT) to noninvasively identify ischemia in patients with suspected CAD has not been sufficiently investigated.This prospective multicenter trial included 254 patients scheduled to undergo clinically indicated ICA for suspected CAD. Coronary CTA was performed before ICA. Evaluation of stenosis (>50% lumen reduction) in coronary CTA was performed by local investigators and in ICA by an independent core laboratory. FFR(CT) was calculated and interpreted in a blinded fashion by an independent core laboratory. Results were compared with invasively measured FFR, with ischemia defined as FFR(CT) or FFR <=0.80.The area under the receiver-operating characteristic curve for FFR(CT) was 0.90 (95% confidence interval [CI]: 0.87 to 0.94) versus 0.81 (95% CI: 0.76 to 0.87) for coronary CTA (p = 0.0008). Per-patient sensitivity and specificity (95% CI) to identify myocardial ischemia were 86% (95% CI: 77% to 92%) and 79% (95% CI: 72% to 84%) for FFR(CT) versus 94% (86 to 97) and 34% (95% CI: 27% to 41%) for coronary CTA, and 64% (95% CI: 53% to 74%) and 83% (95% CI: 77% to 88%) for ICA, respectively. In patients (n = 235) with intermediate stenosis (95% CI: 30% to 70%), the diagnostic accuracy of FFR(CT) remained high.FFR(CT) provides high diagnostic accuracy and discrimination for the diagnosis of hemodynamically significant CAD with invasive FFR as the reference standard. When compared with anatomic testing by using coronary CTA, FFR(CT) led to a marked increase in specificity. (HeartFlowNXT-HeartFlow Analysis of Coronary Blood Flow Using Coronary CT Angiography [HFNXT]; NCT01757678).
EVALuna2:11982